Hair Growth Promoting Activity of Green Tea Leaves (Camellia sinensis l.) Ethanolic Extract - Vini Noviani; Shelly Thauresia; Elsa Fitria Apriani; Partomuan Simanjuntak (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Hair loss and baldness is one of the abnormalities in the hair that often occurs in both men and women. Many cosmetic products from natural to synthetic materials have been developed to overcome these problems, yet, synthetics product is potential to give side effects, such as local irritation. In this study, green tea (Camellia sinensis L.) leaves were used as active substances. The aim of this study was to attest the hair growth promoting activity of n-hexane, water, and ethyl acetate fractions from ethanolic extract of green tea leaves. Green tea leaves contain flavonoids which can help promoting hair growth. To obtain the compound, green tea leaves were made into ethanolic extract. The extract was obtained by maceration using 70% ethanol then partitioned using n-hexane, ethyl acetate, and water, to obtain the n-hexane, ethyl acetate, and water fractions. Ethyl acetate and water fractions have been shown to contain flavonoids, so it could continue the hair growth promoting activities with concentrations of 1% and 4%. Hair growth promoting activity was performed on rabbits. The results showed that 4% of water fraction containing flavonoids had the best hair growth promoting activity.